ANCA-associated vasculitis with cardiac valve vegetations in two teenage males: two case reports and a literature review - Alexandra Theisen; Carrie L. Phillips; Martha Rodriguez (BMC, 2022)
Abstract Background Anti-neutrophil cytoplasm antibody (ANCA)-associated vasculitis is a term used to describe systemic vasculitides that affect small and medium-sized blood vessels. Granulomatosis with Polyangiitis (GPA), a type of ANCA-associated vasculitis (AAV), is rare in children with an estimated prevalence of 3-4 per million, and even more rare is the manifestation of cardiac abnormalities secondary to ANCA-associated vasculitis in the pediatric population. Case presentation We discuss the cases of two teenage males who presented with cardiac valvular lesions secondary to GPA in addition to sinus, pulmonary, renal, and cutaneous involvement. These findings of cardiac valvular abnormalities in GPA have rarely been described in the literature in pediatrics. Both patients were treated with rituximab, high-dose methylprednisolone, and therapeutic plasma exchange and showed improvement in their disease manifestations. Conclusions A review of the literature revealed only five pediatric cases of ANCA-associated vasculitis with cardiac manifestations, and interestingly, three of the five had valvular involvement. Subsequent valvular involvement makes obtaining the diagnosis of ANCA-Associated Vasculitis difficult due to concern for underlying infectious endocarditis and can lead to misdiagnosis given the rarity of cardiac involvement in ANCA-associated vasculitis. Routine echocardiogram is not always completed in newly diagnosed AAV, yet cardiac involvement can lead to severe consequences as was seen with our first patient in the form of thromboembolic stroke. We discuss the importance of keeping AAV on the differential when cardiac lesions are present as well as the importance of regular cardiac screening in newly diagnosed patients with AAV, as it is a major factor of cardiac morbidity and mortality in the adult population and can contribute substantially to management decisions.